Exploring the ripple effect: learner psycho-social challenges, teacher emotional fatigue, and the role of school social work in South Africa-an interview-based qualitative study using Bronfenbrenner's framework - C. Joubert; Susanne Jacobs (Springer, 2024)
Abstract Guided by Bronfenbrenner's (1994) ecological systems theory Bronfenbrenner (Int Encycl Educ,3(2):37-43) , this study highlights the interplay between learner psycho-social challenges and teacher emotional fatigue, which affect classroom dynamics, and the critical role of systemic support-the role of school social workers (SSWs)-in South Africa. Using an exploratory-descriptive qualitative design, we conducted semi-structured interviews with 15 primary school teachers and 13 SSWs from various provinces. Our participants' diverse backgrounds and experiences provided comprehensive insights. Findings highlight the need for a holistic approach to addressing learner psycho-social challenges, emphasising comprehensive support systems for teachers, including training and early intervention. Additionally, the integration of full-time SSWs and the active involvement of psychologists, families, and communities is crucial. Insights can inform educational policies and practices, enhancing teachers' and learners' well-being and effectiveness.